2015
DOI: 10.3390/su8010002
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Interdependence and Cooperative Behaviors on Buyer’s Satisfaction in the Semiconductor Component Supply Chain

Abstract: Abstract:The semiconductor industry is characterized by extreme competition in price and product features. Firms need to acquire or exchange resources with their supplier or buyer partners to stay at the leading edge of technology. Cooperation between buyers and suppliers is important and power is the mechanism that can explain the cooperative behaviors. This study aims to investigate how the power structure between the buyer and supplier influences the extent of suppliers' cooperative behaviors, and the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
(80 reference statements)
0
4
0
Order By: Relevance
“…Nevertheless, the relationship between decision-making in quality improvement and power structure remains an important aspect worth observing. Past studies found that supplier and buyer are more contingent toward each other if the buyer's production quality is dependent on the components from supplier (Pai and Yeh 2016). In another example from the retail industry, it is found that private labels' prices and sales are not affected with major brands' competitive pricing strategies, because of private labels' known quality that generates customer loyalty.…”
Section: Decisions Of Quality and Standardizationmentioning
confidence: 97%
“…Nevertheless, the relationship between decision-making in quality improvement and power structure remains an important aspect worth observing. Past studies found that supplier and buyer are more contingent toward each other if the buyer's production quality is dependent on the components from supplier (Pai and Yeh 2016). In another example from the retail industry, it is found that private labels' prices and sales are not affected with major brands' competitive pricing strategies, because of private labels' known quality that generates customer loyalty.…”
Section: Decisions Of Quality and Standardizationmentioning
confidence: 97%
“…Any potential cooperation success depends on how well it was communicated. Higher-performing partners communicate information more often and with more relevance due to deeper relationships (Pai & Yeh, 2015). More effective partnerships were anticipated to have a better quality of communication, more information exchange between both parties and greater partner involvement in planning and goal formulation.…”
Section: C) Communication (Com)mentioning
confidence: 99%
“…This study is hitched on the social exchange theory. The concept of social exchange has suggested that interdependence reduces risks and encourages cooperation to achieve successful logistics relationships (Lambe, Wittmann & Spekman 2001;Pai & Yeh 2015). In this regard, the study will focus on a variety of ways that different organisations work together in preparedness, disaster response and recovery stages of disaster management at a country level.…”
Section: Humanitarian Supply Chains Risks and Cooperationmentioning
confidence: 99%